Georisks in railway systems under climate uncertainties by different types of sleeper/crosstie materials - S. Kaewunruen; L.M. Cortes Lopes; M.P. Papaelias (Lowland Technology International, 2018)
Railways have been a critical catalyst for economic and social growth around the world. They have been built using local materials to effectively suit whole-life design, construction and maintenance. The choice of construction materials often affects the life cycle performance and plays a key role in resilience of rail assets and infrastructure in an uncertain setting derived from geotechnical risks, operational changes, natural hazards and climate change effects. Nowadays, in railway industry, various materials are being installed in railway tracks as supporting structure. Railway sleepers or ties are an important element, which redistributes wheel load onto track foundation and importantly secures rail gauge. Among them is manufactured by steel, timber, polymer, composite and concrete. The choice of these sleeper materials is mainly arisen from local suitability and compatibility in a specific railway network. This research is the world first to investigate the georisks and potential consequences on track capacity and performance of railway systems under climate uncertainties. Risk analysis and ranking has been conducted using rigorous evidences from critical literature review and expert interviews. This paper highlights track failure modes, short-term and long-term stability, and ground-borne vibration, which causes excessive maintenance and service downtime. The insight into the influence of sleeper material choice will help saving life cycle costs and reducing carbon footprint from repetitive track reconstruction activities.